Hydrodynamics and hydrogeochemistry of Werenskiold Glacier forefield, SW Spitsbergen - Modelska, Magdalena; Buczyński, Sebastian (Polish Polar Research, 2023)
In the 2008 ablation season, subglacial springs discharge, flow rate and profiling of the proglacial river, physical-chemical parameters (pH, temperature, electrical conductivity) and chemical composition (HCO3−, SO42−, Cl−, NO3−, NO2−, PO43−, Ca2+, Mg2+, Na+, K+, Fetot, Mn2+, Al3+, Zn2+, Pb2+ and SiO2) of water in the Werenskiold Glacier forefield were measured. Chemical composition of groundwater as well as water of lakes, the main watercourse, subglacial outflows and water representing direct meltwater recharge were studied to determine their origin, the depth of circulation and recharge systems. The results indicate that the main source of water in the glacial river were the subglacial outflows in the central part of the glacier. They generated 77% of the total amount of water in the glacier forefield. Direct inflow of groundwater from glacier moraine to proglacial river was marginally low and the water circulation system was shallow, fast and variable. There were no evidences for an important role of deeper than suprapermafrost water circulation systems. The water temperature, especially in the lakes, exceeding the mean daily air temperature during the ablation period, is due to the heating of the ground moraine rocks. A clear difference between groundwater chemical composition and surface water as well as subglacial runoff in terms of major ions, together with the homogeneity of chemical composition of the proglacial river from spring to mouth confirmed the marginal role of groundwater runoff in the drainage of the catchment area. It was confirmed that the chemical composition of groundwater and moraine lakes in the glacier forefield was shaped by geological factors, i.e., mainly chemical weathering of sulphides, carbonates and secondary sulphates. The possibility of secondary iron hydroxide precipitation and a high probability of complex aluminosilicate transformations were also demonstrated.